Intellectual capital in non-profit organisations: lessons learnt for waqf institutions - Abdelkader Laallam; Salina Kassim; Engku Rabiah Adawiah Engku Ali; Buerhan Saiti (ISRA International Journal of Islamic Finance, 2020)
Purpose: This study aims to highlight the importance of intellectual capital (IC) for the operation of waqf (Islamic endowment) institutions, as few studies have discussed this issue in relation to non-profit religious organisations, particularly waqf organisations. Consequently, this study hopes to contribute to the development of waqf institutions in terms of human capital proficiency, the efficiency of operations and the effectiveness and sustainability of performance. Design/methodology/approach The authors reviewed a significant body of relevant studies written on various aspects of IC, to highlight the significance of considering IC in the operation of non-profit organisations (NPOs) and waqf institutions. Findings This study highlights the importance of IC in the operation of waqf institutions. It provides a platform that facilitates understanding of the existing obstacles and challenges in waqf institutions (such as lack of accountability, lack of funding, mismanagement and lack of trained labour, among others) and offers potential solutions through the consideration of knowledge and IC. Research limitations/implications This study is a conceptual analysis of IC in the context of NPOs. Future studies should conduct empirical testing, which will provide more detailed discussion and enriching insights into the issue of IC and the performance of NPOs, particularly in the case of waqf institutions. Practical implications This study provides several important implications for waqf institutions and other NPOs, as it sheds light on the consideration of knowledge and IC in their operations. Originality/value To the best of the authors' knowledge, this study is the first to discuss the issues of waqf in the light of IC and provide an integrated framework for the operation of waqf institutions.
Keywords: 330; Organisational performance; Intellectual capital; Islamicfinance; Non-profit organisations; Waqf institutions